Cyclic Tensile Strain Can Play a Role in Directing both Intramembranous and Endochondral Ossification of Mesenchymal Stem Cells - Carroll, Simon F.; Buckley, Conor T.; Kelly, Daniel J. (Frontiers in Bioengineering and Biotechnology, 2017)
Successfully regenerating damaged or diseased bone and other joint tissues will require a detailed understanding of how joint specific environmental cues regulate the fate of progenitor cells that are recruited or delivered to the site of injury. The goal of this study was to explore the role of cyclic tensile strain (CTS) in regulating the initiation of mesenchymal stem cell/multipotent stromal cell (MSC) differentiation, and specifically their progression along the endochondral pathway. To this end, we first explored the influence of CTS on the differentiation of MSCs in the absence of any specific growth factor, and secondly examined the influence of the long-term application of this mechanical stimulus on markers of endochondral ossification in MSCs maintained in chondrogenic culture conditions. A custom bioreactor was developed to apply uniaxial tensile deformation to bone marrow-derived MSCs encapsulated within physiological relevant 3D fibrin hydrogels. Mechanical loading, applied in the absence of soluble differentiation factors, was found to enhance the expression of both tenogenic (TNC, COL1A1) and osteogenic markers (BMP2, RUNX2 and ALPL), while suppressing markers of adipogenesis. No evidence of chondrogenesis was observed, suggesting that CTS can play a role in initiating direct intramembranous ossification. During longer term culture in the presence of a chondrogenic growth factor, CTS was shown to induce MSC re-organization and alignment, increase proteoglycan and collagen production, and to enhance the expression of markers associated with endochondral ossification (BMP2, RUNX2, ALPL, OPN, COL10A1) in a strain magnitude dependent manner. Taken together, these findings indicate that tensile loading may play a key role in promoting both intramembranous and endochondral ossification of MSCs in a context dependent manner. In both cases this loading induced promotion of osteogenesis correlated with an increase in the expression of the osteogenic growth factor BMP2. The results of this study demonstrate the potent role that extrinsic mechanical loading plays in guiding stem cell fate, which must be carefully considered in the design of cell and tissue engineering therapies if they are to realize their clinical potential.